Mary Jane's ghost : the legacy of a murder in small town America - Gregory, Ted (University Of Iowa Press, 2017)
"Summer 1948. In the scenic, remote river town of Oregon, Illinois, a young couple visiting the local lovers' lane is murdered. The shocking crime garners headlines from Portland, Maine, to Long Beach, California. But after a sweeping manhunt, no one is arrested and the violent deaths of Mary Jane Reed and Stanley Skridla fade into time's indifference. Fast forward fifty years. Eccentric entrepreneur Michael Arians moves to Oregon, opens a roadhouse, gets elected mayor, and becomes obsessed with the crime. He comes up with a scandalous conspiracy theory and starts to believe that Mary Jane's ghost is haunting his establishment. He also reaches out to the Chicago Tribune for help. Arians's letter falls on the desk of general assignment reporter Ted Gregory. For the next thirteen years, while he ricochets from story to story and his newspaper is deconstructed around him, Gregory remains beguiled by the case of the teenaged telephone operator Mary Jane and twenty-eight-year-old Navy vet Stanley--and equally fascinated by Arians's seemingly hopeless pursuit of whoever murdered them. Mary Jane's Ghost is the story of these two odysseys"--